Abstract 5269: Minor Variant Finder: New software for detecting somatic mutations at low level in Sanger sequencing traces - Schreiber, Edgar H.; Leong, Harrison; Schneider, Stephanie J.; Jeff, Marks; George, Wallace; Sangha, Hardeep; Lim, Yoke Peng; Chan, Evelyn; Berosik, Steve; Storm, Martin; Colburn, Joel (Cancer research (Chicago, Ill.), 2016)
Introduction: With the rapid adoption of next generation sequencing (NGS) and its use for characterization of mutations in tumor samples, a need has emerged to establish an orthogonal technology for reliable and sensitive detection of somatic mutations which may occur at proportions of 10% or lower compared to the normal allele. Until now, somatic variants with an allelic proportion of 25% or less are often undetected (i.e. not “called”) by automated Sanger sequencing software. We have developed Minor Variant Finder software that calls 5% minor variants at 96% sensitivity and 99% specificity in a test data set. The improved variant detection software calls variants de novo, without a priori knowledge of location or presence, and affords all the advantages of Sanger sequencing, of robustness, low error rate, ease of use, human interpretable visual displays of the output data, and low cost per sample and target. Methods: New algorithms were developed to compare and subtract the baseline noise signals of a control sample from a test sample. Noise minimization and peak detection algorithms enable the detection of peaks representing candidate minor variants which are confirmed in the complementary strand.To test the new algorithms, synthetic mixtures of minor alleles in the range of 2.5%, 5%, 10% and 20% were prepared by combining genomic DNAs containing known mutations. Using an optimized PCR/sequencing protocol to sequence cell line and FFPE derived DNA, 13 different amplicons and seven different genes, including P53, KRAS, BRAF, FLT3, RB1, CDH1, and ERBB2, were sequenced on 3500, 3730, and 3130 Applied Biosystems Genetic Analyzers. Results: To test the new software, 898,499 total base positions and 3126 total variant positions, spanning variants at 2%, 5%, 10%, and 20%, were interrogated. The software achieved 96% sensitivity and 99.8% specificity for automated detection of 1112 variants present at the 5% level in 274,110 high quality base positions. Sensitivity was 99% for variants at 10%, and 99.7% for variants at 20%. The software displays a noise-minimized trace view to facilitate visual inspection for confirmation or rejection. Further, reference sequences with hg19 chromosomal locations and NGS vcf files can be imported and aligned side by side with the Sanger sequencing data for orthogonal verification. Hyperlinks to dbSNP for known rsSNP variants are provided in the software. Conclusions: We have developed new Minor Variant Finder software that detects and reports minor variants by Sanger sequencing. We have demonstrated that the new software used in conjunction with standard protocols for fluorescent dye terminator Sanger sequencing enable the identification of de novo somatic mutations to a level of 5% with 96% sensitivity and 99.81% specificity. This technology will also be useful for the confirmation of minor variants identified by NGS. For Research Use only - Not for use in diagnostic procedures. Citation Format: Edgar H. Schreiber, Harrison Leong, Stephanie J. Schneider, Marks Jeff, Wallace George, Hardeep Sangha, Yoke Peng Lim, Evelyn Chan, Steve Berosik, Martin Storm, Joel Colburn. Minor Variant Finder: New software for detecting somatic mutations at low level in Sanger sequencing traces. [abstract]. In: Proceedings of the 107th Annual Meeting of the American Association for Cancer Research; 2016 Apr 16-20; New Orleans, LA. Philadelphia (PA): AACR; Cancer Res 2016;76(14 Suppl):Abstract nr 5269.